Issues in transferring education research across dental schools. Issue 12 (23rd November 2021) - Chambers, David W.
Abstract : Issue: Almost all dental educational research describes statistically significant changes using a one‐time intervention at a single program. It is hoped that the most significant of these interventions will transfer to other schools. Approach: But the research logic of context‐specific investigations does not always generalize with the same impact to new situations. This is the transfer problem. There is virtually no systematic research exploring the extent to which transfer from the dental educational literature is attempted, how successful it is, and what factors improve transfer. Impact: The paper discusses some of the more prominent issues in transferability such as (a) the meaning of "identical" conditions upon which inductive statistics are based, (b) isolation of causal factors, (c) generalizability, (d) reliability and validity, (e) measures of effect, (f) statistical versus practical significance, and (g) the need to build theory in discussion sections. Eight suggestions are offered for making dental educational research more transferable.